VEGETABLE SELLER REGISTER : ANALYSIS LANGUAGE IN KAHAYAN MODERN TRADITIONAL MARKET PALANGKARAYA MUNICIPALITY - Nur Maulinawati; Imam Qalyubi; Akhmad Ali Mirza (PROJECT (Professional Journal of English Education), 2022)
Language variations in terms of usage are known as registers. This study examines the form and meaning of registers of vegetable traders in the modern traditional Kahayan market of Palangkaraya Municipality. Descriptive qualitative method was used in this research which involved five informants in Kahayan Modern Traditional Market Palangkaraya Municipality based on sampling technique the criteria needed. Collecting the data, the researcher utilized three instruments  which  were observation, interview and documentation. (1) This study attempts to describe the form of registers of vegetable traders in the modern traditional Kahayan market, Palangkaraya Municipality. (2) This  study attempts to describe the meaning of the register of vegetable traders in the modern traditional Kahayan market, Palangkaraya Municipality. The data were analyzed using the listen, note and tapping technique. Data were analyzed using triangulation method. The results of this study are that the first is that there is a clitic form of the entlithic type and the phrase. Second, the meaning of registering vegetable traders in the traditional Kahayan market, Palangkaraya, Kota Madya, is instrumental, provides an opportunity, and interaction function shows feelings. Keywords:  Vegetable Seller Register, Analysis Language, and Traditional Market